2007
DOI: 10.1124/jpet.106.115436
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of a Potent, Selective Leukotriene A4 Hydrolase Inhibitor in Comparison with the 5-Lipoxygenase Inhibitor Zileuton

Abstract: Leukotriene A 4 hydrolase (LTA 4 H) catalyzes production of the proinflammatory lipid mediator, leukotriene (LT) B 4 , which is implicated in a number of inflammatory diseases. We have identified a potent and selective inhibitor of both the epoxide hydrolase and aminopeptidase activities of recombinant human LTA 4 H (IC 50 , approximately 10 nM). In a murine model of arachidonic acid-induced ear inflammation, the LTA 4 H inhibitor, JNJ-26993135 (1-[4-(benzothiazol-2-yloxy)-benzyl]-piperidine-4-carboxylic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 24 publications
5
88
1
2
Order By: Relevance
“…8). In agreement with our results, blocking LTA 4 hydrolase, the enzyme responsible for converting LTA 4 to LTB 4 , leads to anti-inflammatory effects mediated by an increase in LXA 4 production (61,62). Our data also support the idea that LXA 4 deficiency plays a role in the development of obesity and its complications.…”
Section: Discussionsupporting
confidence: 81%
“…8). In agreement with our results, blocking LTA 4 hydrolase, the enzyme responsible for converting LTA 4 to LTB 4 , leads to anti-inflammatory effects mediated by an increase in LXA 4 production (61,62). Our data also support the idea that LXA 4 deficiency plays a role in the development of obesity and its complications.…”
Section: Discussionsupporting
confidence: 81%
“…One week after infusion, mice were treated with a single LPS administration and then subjected to Western blot assay. Quantification of Western blot showed that infusion of LVCysLT 1 R-shRNA-EGFP but not LV-EGFP significantly suppressed the LPS-induced increase in CysLT 1 R expression in the mouse hippocampus (F (3,12) =30.01, Veh+Veh vs Veh+LPS: P=0.0013; Veh+LPS vs LV-EGFP+LPS: P=0.747; Veh+LPS vs LV-CysLT 1 R-shRNA-EGFP+LPS: P<0.001; Figure 1D, 1E).…”
Section: Resultsmentioning
confidence: 99%
“…They exert effects through cell surface receptors, such as cysteinyl leukotriene receptor 1 (CysLT 1 R). Leukotriene pathway modifiers, including 5-lipoxygenase inhibitor (zileuton) and CysLT 1 R antagonists (montelukast, zafirlukast, and pranlukast), have been used as anti-asthmatic drugs [11][12][13] . Recently, several studies on CysLT 1 R have focused on its novel pathophysiological role in CNS disorders, such as cognitive impairment [14] , cerebral ischemia [15] , brain trauma [16] and experimental autoimmune encephalomyelitis [17] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…Inhibition of LTA 4 hydrolase selectively inhibits LTB 4 formation while increasing LXA 4 synthesis in a mouse model of zymosan-induced peritonitis. In addition, inhibition of LTA 4 hydrolase was found to attenuate allergic airway inflammation, thereby increasing LXA 4 levels in the bronchoalveolar lavage fluid of mice (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these enzymes might elevate available LTA 4 for LX synthesis while inhibiting proinflammatory LTs. This has already been shown for LTA 4 hydrolase inhibition in mouse models of inflammation (32,33). The PMNL/platelet coculture system represents a suitable in vitro system to test the influence of LT synthase inhibitors on LX synthesis.…”
Section: Flap and 5-lo Expression Is Decreased In M2 Macrophagesmentioning
confidence: 99%